What do students know about evolution by natural selection after a non-majors geology course? An analysis of student responses to open-ended questions. Issue 3 (26th July 2021) - Harding, Rachel L. S.; Williams, Kurt R.; Forcino, Frank L.; Dees, Jonathan; Pennaz, Madelyn; Momsen, Jennifer L.
Abstract: Most of the research on student understanding of evolution by natural selection has focused on undergraduate biology courses for science majors. However, the majority of undergraduates in the United States will not enroll in a biology course for majors. In this study, we identify the extent of natural selection understanding that students acquire through an undergraduate, non-majors geology course. Using a pre/post assessment model, we administered open-response items from the Bishop and Anderson Diagnostic Instrument and a religiosity scale. Student responses were coded for inclusion and correctness of five key principles of natural selection: variation in a population, origin of variation, inheritance, fitness, and change in a population over time. The majority of students included few, if any, key principles of natural selection in their responses prior to instruction, and improvement after direct instruction in their geology course was minimal (cheetah: mean pre 1.01, mean post 1.37; salamander: mean pre 0.79, mean post 1.15). In most cases, students' self-reported religiosity was unrelated to their knowledge of natural selection. Together, our results demonstrate that in spite of instruction, non-majors geology students struggle to describe the process of natural selection using foundational principles. We encourage the continued development of cross-disciplinary educational resources for this important population to help all students, regardless of major or career path, gain a more robust understanding of evolution by natural selection.